Hepatitis C Virus and Nonliver Solid Cancers: Is There an Association between HCV and Cancers of the Pancreas, Thyroid, Kidney, Oral Cavity, Breast, Lung, and Gastrointestinal Tract? - Saad Qadwai; Tayyaba Rehman; Jonathan Barsa; Zeeshan Solangi; Edward Lebovics (Gastroenterology Research and Practice)
Hepatitis C virus (HCV) is known for its oncogenic potential and has been found to be associated with hepatocellular carcinoma (HCC) and non-Hodgkin lymphoma. It has also been postulated that HCV may play a role in the development of other extrahepatic solid tumors of other organs of the body since it has been isolated from the vessel wall, kidney, and oral mucosa. In this article, we have reviewed epidemiological studies that have been done to look into the relationship of HCV with nonliver solid cancers of the pancreas, thyroid, renal, oral cavity, breast, and lung and nonpancreatic gastrointestinal cancers. Based on this review, HCV might be associated with an increased risk of renal cell and lung cancers.